Nilai Pendidikan Karakter Cerpen Luh Ayu Manik Mas Tresna Ring Alas Karya I Made Sugianto - Putra, Made Fandy Darma; Arini, Ni Wayan (Metta : Jurnal Ilmu Multidisiplin, 2024)
Short stories are cases of modern Balinese literature which cannot be separated from traditional Balinese literature which must be taught more deeply and the values ​​contained therein are applied. In this research, the short story entitled Luh Ayu Manik Mas Tresna Ring Alas will be studied. This short story contains a very good meaning for teaching children to care about the environment. The aim of this research is to determine the intrinsic elements and values ​​of character education contained in the short story Luh Ayu Manik Mas Tresna Ring Alas. This research uses qualitative research with a descriptive approach. The data collection methods used were interviews, literature and documentation. The results obtained from the short story Luh Ayu Manik Mas Tresna Ring Alas are intrinsic elements such as; theme, namely environmental heroes, incidents, namely there are ten incidents, there are three settings, namely place setting, time setting, and socio-cultural background, characters and characterization are divided into two, namely main characters and additional characters, the plot used is a mixed plot, the message contained in This short story states that we as Balinese people should be able to develop and preserve the existence of plants so that the island of Bali becomes shadier. The character education values ​​contained in this research are; honest, disciplined, hardworking, creative, independent, curious, appreciates achievements, friendly/ communicative, likes to read, cares about the environment, and is responsible.